K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 8 2019

a) x(x - 3) + 2 = 0

=> x2 - 3x + 2 = 0

=> x2 - 2x - x + 2 = 0

=> x(x - 2) - (x - 2) = 0

=> (x - 1)(x - 2) = 0

=> \(\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}}\)

=> \(\orbr{\begin{cases}x=1\\x=2\end{cases}}\)

b) x(x - 5) + 3x - 7 = 0

=> x2 - 5x + 3x - 7 = 0

=> x2 - 2x - 7 = 0

=> (x - 1)2 = 8

=> \(\orbr{\begin{cases}x-1=8\\x-1=-8\end{cases}}\)

=> \(\orbr{\begin{cases}x=6\\x=-7\end{cases}}\)

27 tháng 8 2019

a)  \(B=-x^2+4x-6=-\left(x^2-4x+6\right)\)

\(-\left(x^2-4x+4\right)-2=-\left(x-2\right)^2-2\le-2\forall x\)

b) \(B\le-2\forall x\)nên GTLN của B là -2\(\Leftrightarrow x=2\)

27 tháng 8 2019

\(\left(a+b\right)^2=a-b=7^2ab=10\)

\(\Rightarrow a^2-2ab+b^2=7\times8\)

\(\Rightarrow a^2+b^2+2ab=2.10=56\)

\(\Rightarrow a^2+b^2=56\)

\(\Rightarrow a^2+2ab+2b^2=56+2.10=76\)

Vậy sẽ bằng 76

b Tương tự